A Device to Measure the Oxygen Uptake Rate of Attached Cells: Importance in Bioartificial Organ Design - Brent D. Foy; Avi Rotem; Mehmet Toner; Ronald G. Tompkins; Martin L. Yarmush (Cell Transplantation, 1994)
Quantification of the dependence of cellular oxygen uptake rate (OUR) on oxygen partial pressure is useful for the design and testing of bioartificial devices which utilize cells. Thus far, this information has only been obtained from suspended cells and from cells attached to microcarriers. In this work, a device was developed to obtain the dependence of OUR on oxygen partial pressure for anchorage-dependent cells cultured in standard culture dishes. The device is placed and sealed on the top of the culture dish, and holds a Clark polarographic mini-electrode flush with the bottom surface of the device. It also houses a motor to spin a magnetic stir bar within the cell chamber to insure that the medium is well-mixed. Several characteristics of the device — such as oxygen leakage into the device chamber, electrode-lag time, and linearity of the electrode at low oxygen partial pressures-were quantified and their potential effect on the values of V m (maximal OUR) and K 0.5 (oxygen partial pressure at which OUR is half-maximal) were evaluated. Comparison of V m and K 0.5 values obtained with this device with previously published values for suspended rat hepatocytes, Bacillus cereus, and E. coli indicated that the technique provides values accurate within 30% as long as the cell under study has a K 0.5 greater than approximately 1.0 mmHg. For hepatocytes cultured on 0.05 mm thickness collagen gel for 1 day (n = 4) and 3 days (n = 6), V m was found to be 0.38 ± 0.12 and 0.25 ± 0.09 nmol O 2 /s/106 cells, respectively, and K 0.5 was found to be 5.6 ± 0.5 and 3.3 ± 0.6 mmHg, respectively. This technique should aid in predicting bioreactor conditions such as flow rate, cell density, distance of cell from flow, and gas phase oxygen partial pressure which can lead to oxygen limitations. In addition, further studies of the effect of factors such as extracellular matrix composition, metabolic substrate, and drugs on the dependence of OUR on oxygen partial pressure for many anchorage-dependent cell types can be pursued with this technique.